DOES FINANCIAL DISTRESS PREMIUM EXIST IN ASSET PRICING? TESTING AN AUGMENTED SIX-FACTOR MODEL IN PAKISTAN’S EQUITY MARKET - LUQMAN KHAN , DR. MUSTAFA AFEEF (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
In recent years, the rapid and significant development of non-financial sector in Pakistan has globally led potential investors and academicians assess the markets in terms of risk inheritance. Therefore, this study aims to explore the validity and applicability of the Augmented Financial Distress Six-Factor Model namely Fama-Franch Six Factor in Pakistan’s stock market for the period of June-2010 to June-2023. This study collects data on 202 non-financial firms listed on the Pakistan Stock Exchange, namely the KSE-100 Index, and follows Fama-Franch regression methodology for empirical estimation. The findings of this study conclude that small portfolios (small size companies) earn considerably higher returns than big portfolios (large size companies). Ultimately, the risk associated with portfolio returns is reported to be higher for small portfolios (small size companies) than for big portfolios (large size companies). According to the regression output, the FF Six-factor model was found to be valid for explaining time series variation in excess portfolio returns. Later, we added financial distress model in over study. This study found that the human capital based six factor model outperformed the other financial distress models. The findings of the study indicate that small portfolios earn more returns than big portfolios to reward the investor for taking extra risks. Investors may benefit by timing their investments to maximize stock returns. Company investment in financial distress adds reliable information that replicates the value of the company, and in the long term, helps investors make rational decisions.